2013
DOI: 10.1002/bit.24816
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an inducible cell‐communication system that amplifies Salmonella gene expression in tumor tissue

Abstract: Bacterial therapies have the potential to overcome resistances that cause chemotherapies to fail. When using bacteria to produce anticancer agents in tumors, triggering gene expression is necessary to prevent systemic toxicity. The use of chemical triggers, however, is hampered by poor delivery of inducing molecules, which reduces the number of activated bacteria. To solve this problem, we created a cell-communication system that enables activated bacteria to induce inactive neighbors. We hypothesized that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…In humans, antibiotics could not be used, and the ZsGreen construct would have to be maintained with a balanced lethal system or be incorporated into the Salmonella genome. 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…In humans, antibiotics could not be used, and the ZsGreen construct would have to be maintained with a balanced lethal system or be incorporated into the Salmonella genome. 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al inserted the inv gene downstream of the lux quorum system, which showed that invasiveness depended on the multiplicity of infection and was comparable to that of the constitutive construct [72]. A recent publication reported integration of the pBAD promoter into the quorum sensing system, which enabled bacteria to activate neighbors and increased the time scale of protein production [73].…”
Section: Controllable Gene Expressionmentioning
confidence: 98%
“…Overcoming these obstacles is important to move BMCT closer to clinical application in the future. [7,10,71,72] pTet Tetracylin [30] RecA Radiation [12] Quorum sensing Bacterial density [72,73] Hypoxia-inducing promoters Low oxygen condition [11,20,72,74,75] …”
Section: An Ideal Bug For the Futurementioning
confidence: 99%
“…A similar strategy has also been employed to amplify the expression of the desired protein induced with small molecules (e.g. L-arabinose) that diffuse poorly within the tumor mass [39]. Bacteria have also been engineered to silence the expression of important genes related to tumor development through RNA interference.…”
Section: Engineered Bacteria Against Cancermentioning
confidence: 99%